Correlation between saturated fatty acid chain-length and intermolecular forces determined with terahertz spectroscopy. Issue 25 (11th March 2019) - Fan, Shuting; Ruggiero, Michael T.; Song, Zihui; Qian, Zhengfang; Wallace, Vincent P.
Abstract : Chain-length dependent intermolecular interactions of saturated fatty acids are directly probed with THz-TDS and confirmed by ab initio calculations. Abstract : We measured crystalline (C-form) saturated fatty acids with even carbon numbers ranging from 12 to 20 using temperature dependent terahertz time-domain spectroscopy (THz-TDS). Absorption features between 0.5 and 3 THz were identified at temperatures from 96 K to 293 K, and a systematic red-shift was obvserved with the increasing carbon chain length. The origins of these absorption bands were uncovered using state-of-the-art ab initio density functional theory (DFT) calculations. Similar vibrational motions in the absorption bands of the different materials highlight the unique role that THz-TDS has for probing weak non-covalent interactions in these materials. Our results showcase the utility of the terahertz region, which is beyond the scope of related vibrational techniques, providing direct evidence of the effect of chain length on the intermolecular interactions of these molecules.